Bacteria Pseudomonas taiwanensis as a decomposing agent of peat fiber - Gulo, Elrich Gratiawan WD; Amalia , Dewi; Mase, Lindung Zalbuin; Yulianto, Faisal Estu; Kusuma, Yusmiati; Juarti, Ery Radya; Suyono, Agus (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2023)
Efforts are needed to accelerate the decomposition of peat fiber to reduce the fiber content through bioaugmentation using Pseudomonas taiwanensis bacteria so that it can reduce the high-water content of peat fiber. The research aimed to determine the effect of adding Pseudomonas taiwanensis bacteria on the decomposition of peat fiber. This research is a laboratory experimental research. The research sampling location was in Bereng Bengkel Village, Palangkaraya. The parameters observed included fiber content, fiber size distribution, and peat fiber decomposition speed following the Peat Testing Manual. The research instrument was an observation sheet for fiber content, size distribution, and peat fiber decomposition speed. Research data was analyzed using descriptive statistical analysis. The results showed that adding 15% Pseudomonas taiwanensis bacteria with a curing period of 28 days in fibrous peat resulted in the highest reduction in fiber content, from the initial condition of 61.14% to 12.33%. This variation also shows a decrease in coarse and medium fiber content and a significant increase in fine fiber content. The decomposition rate for this variation shows good consistency. The conclusion was that adding 15% Pseudomonas taiwanensis bacteria with a curing period of 28 days showed optimal results in accelerating the decomposition of peat fiber through the bioaugmentation method.